Hot deformation and processing map of an as-extruded Mg–Zn–Mn–Y alloy containing I and W phases. (15th December 2015) - Tahreen, N.; Zhang, D.F.; Pan, F.S.; Jiang, X.Q.; Li, D.Y.; Chen, D.L.
Abstract: The hot deformation characteristics of an as-extruded ZM31 (Mg–Zn–Mn) magnesium alloy with an addition of 3.2 wt.% Y, namely ZM31 + 3.2Y, have been studied via isothermal compression testing in a temperature range of 300–400 °C and a strain rate range of 0.001–1 s − 1 . A constitutive model based on hyperbolic-sine equation along with processing maps was used to describe the dependence of flow stress on the strain, strain rate, and deformation temperature. The flow stress was observed to decrease with increasing deformation temperature and decreasing strain rate. The deformation activation energy of this alloy was obtained to be 241 kJ/mol. The processing maps at true strains of 0.1, 0.2, 0.3 and 0.4 were generated to determine the region of hot workability of the alloy, with the optimum hot working parameters being identified as deformation temperatures of 340–500 °C and strain rates of 0.001–0.03 s − 1 . EBSD examinations revealed that the dynamic recrystallization occurred more extensively and the volume fraction of dynamic recrystallization increased with increasing deformation temperature. The role of element Y and second-phase particles (I- and W-phases) during hot compressive deformation was discussed. Graphical abstract: Highlights: Deformation activation energy of ZM31 + 3.2Y alloy is obtained to be 241 kJ/mol. Cross-slip of screw dislocations is identified as the rate-controlling mechanism. Processing maps at different deformation amounts are constructed. The optimal deformation condition is observed to be 340–500 °C at 0.001–0.03 s − 1 . During hot deformation dynamic recrystallization occurs.